2010
DOI: 10.1007/s11259-010-9448-4
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergence of multi-drug resistant Salmonella enterica serovar Stanley from cattle

Abstract: During 2009, Salmonella enterica subspecies enterica serovar Stanley isolates were recovered from cattle diagnostic specimens in southern Japan, and the isolates were examined to characterize the genetic determinants involved in this new pathogenicity that associated with mortality in cattle. All the isolates were multi-drug resistance exhibited resistance to ampicillin, chloramphenicol, streptomycin, sulfamethoxazole, oxytetracycline, and kanamycin (ACSSuT-Km) encoded by blaTEM, catA, aadA1, sul1, tet(A), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In animals, salmonellosis is mainly treated with antibiotics for prevention and control. However, due to the abuse of antibiotics in recent years, the rate of Salmonella with drug resistance and even multidrug resistance has risen significantly resulting in the increased frequency of treatment failure in human clinical medicine (Hidalgo-Vila et al 2008;Kariuki et al 2015;Kingsley et al 2009;Dahshan et al 2011;Beyene et al 2011;Hendriksen et al 2009;Pan et al 2009;Li and Liu 2005). Salmonella with antibiotic resistance in contaminated products could infect humans directly or transmit their resistance genes to human pathogens through the food chain, leading to the failure of antibiotic treatment and posing a threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, salmonellosis is mainly treated with antibiotics for prevention and control. However, due to the abuse of antibiotics in recent years, the rate of Salmonella with drug resistance and even multidrug resistance has risen significantly resulting in the increased frequency of treatment failure in human clinical medicine (Hidalgo-Vila et al 2008;Kariuki et al 2015;Kingsley et al 2009;Dahshan et al 2011;Beyene et al 2011;Hendriksen et al 2009;Pan et al 2009;Li and Liu 2005). Salmonella with antibiotic resistance in contaminated products could infect humans directly or transmit their resistance genes to human pathogens through the food chain, leading to the failure of antibiotic treatment and posing a threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Most human salmonellosis cases are foodborne (Hoelzer et al 2011). Dahshan et al (2011) indicated chance of transmission of antimicrobial-resistant Salmonella to humans through the food chain and a threat to human health in their study of emergence of multidrug-resistant Salmonella Stanley from cattle diagnostic specimens in southern Japan. In Ethiopia, Beyene et al (2011) detected multiply drugresistant Salmonella organisms in their study on etiology of febrile and diarrheic illness in Ethiopian children focusing on Salmonella.…”
Section: Introductionmentioning
confidence: 99%
“…Another gene coding for a protein with 99% identity to the aadA1 gene product from Escherichia coli (Figure 2 subunit 3) is also present. AadA1 is an aminoglycoside-3′-adenylyltransferase that confers resistance to streptomycin and spectinomycin [53]. Finally, there is also a gene that codes a protein which is 98% identical to Aac6 from Enterobacter cloacae , an aminoglycoside phosphotransferase that confers resistance to netilmicin and tobramycin [54].…”
Section: Resultsmentioning
confidence: 99%